The Influence of Self Efficacy on the Interest in Enterprise Students of Ners Stikes Gunung Sari Profession - Nurnainah Nurnainah; Nurnaeni Nurnaeni; Erni Johan (Global Health Science Group, 2022)
This study aims to see the effect of self-efficacy on the interest in entrepreneurship for professional students at Nurse STIKES Gunung Sari. This type of research is quantitative with a cross-sectional approach, namely, research to determine the effect or relationship between two or more variables. When the research was carried out in July–August 2022 at the Gunung Sari Strikes the population in this study was all 2022 nursing professional students, totaling 51 people while the sample used amounted to 45 people. The data used in this study are primary and secondary data. Primary data collection takes the form of historical data about Gunung Sari STIKES, its vision and mission, goals, the facilities and infrastructure of the Gunung Sari STIKES campus, and other data. The research process is described in the academic section of the student affairs section and sections related to research. Secondary data was obtained by distributing questionnaires or questions that had been prepared by the researchers to be further distributed to the Gunung Sari STIKES students directly. There is an influence of self-efficacy on entrepreneurial interests among professional students at Nurse STIKES Gunung Sari.